2004
DOI: 10.1002/pros.20054
|View full text |Cite
|
Sign up to set email alerts
|

Translationally controlled tumor protein (TCTP) in the human prostate and prostate cancer cells: Expression, distribution, and calcium binding activity

Abstract: The results of the present study demonstrate, for the first time, the expression of TCTP in the human prostate and in prostate cancer cells, and suggest the involvement of the protein in key-processes such as apoptosis, cellular differentiation, and in the control of sperm functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(94 citation statements)
references
References 49 publications
3
91
0
Order By: Relevance
“…Later, it was shown that TCTP levels are regulated in response to perturbations of intracellular Ca 2+ -homeostasis (Xu et al 1999). Although TCTP does not have a canonical Ca 2+ -binding site , its Ca 2+ -binding activity has been confirmed by several laboratories using a range of methods (Feng et al 2007a;Graidist et al 2007;Kim et al 2000;Lucas et al 2014;Arcuri et al 2004Arcuri et al , 2005Sanchez et al 1997). However, the different approaches used to map the Ca 2+ -binding site at the TCTP protein yielded different results (Feng et al 2007a;Graidist et al 2007;Kim et al 2000).…”
Section: Involvement In Cellular Stress Responsesmentioning
confidence: 99%
See 2 more Smart Citations
“…Later, it was shown that TCTP levels are regulated in response to perturbations of intracellular Ca 2+ -homeostasis (Xu et al 1999). Although TCTP does not have a canonical Ca 2+ -binding site , its Ca 2+ -binding activity has been confirmed by several laboratories using a range of methods (Feng et al 2007a;Graidist et al 2007;Kim et al 2000;Lucas et al 2014;Arcuri et al 2004Arcuri et al , 2005Sanchez et al 1997). However, the different approaches used to map the Ca 2+ -binding site at the TCTP protein yielded different results (Feng et al 2007a;Graidist et al 2007;Kim et al 2000).…”
Section: Involvement In Cellular Stress Responsesmentioning
confidence: 99%
“…The importance of such a Ca 2+ -buffer-like function for TCTP was described for trophoblast cells of the placenta, where it is involved in Ca 2+ -handling and in its provision for the foetal blood circulation (Arcuri et al 2005). Similarly, in human prostate epithelial cells, TCTP is the Ca 2+ -binding protein with the highest expression levels (Arcuri et al 2004). Another important player in maintaining intracellular ion homeostasis that is influenced by TCTP is the membrane-bound Na + ,K + -ATPase.…”
Section: Involvement In Cellular Stress Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…TCTP overexpression has previously been associated with numerous malignancies. [72][73][74] Immunofluorescent histologic analysis of cells exposed to LB102 exhibited abnormal mitotic figures and distorted microtubules, characteristics of mitotic catastrophe. These in vitro experiments were replicated in U373 GBM cell line with a p53 gain-of-function mutation.…”
Section: Lb100: a Small Molecule Inhibitor Of Pp2amentioning
confidence: 99%
“…It is reported as multifunctional to participate in numerous cellular processes including cell growth, survival, development, protein synthesis, immune response, tumor reversion, transcription regulation, and induction of pluripotent stem cells or apoptosis (Bommer and Thiele 2004). Comparing to normal tissue, the level of TCTP is increased in many human cancer tissues, such as breast, colorectal, prostate and lung cancer (Arcuri et al 2004;Deng et al 2006;Kim et al 2008;Slaby et al 2009). Therefore, in recent years, more and more attention is paid to the involvement of TCTP on tumor reversion because of its critical role in tumorigenesis (Miao et al 2013;Nagano-Ito and Ichikawa 2012).…”
Section: Discussionmentioning
confidence: 99%